2017
DOI: 10.3390/s17122931
|View full text |Cite
|
Sign up to set email alerts
|

Single Interdigital Transducer Approach for Gravimetrical SAW Sensor Applications in Liquid Environments

Abstract: Surface acoustic wave (SAW) devices are well known for mass-sensitive sensor applications. In biosensing applications, chemical and biochemically evoked binding processes on surfaces are detected in liquid environments using delay line or resonator sensor configurations, preferably in combination with the appropriate microfluidic devices. All configurations share the common feature of analyzing the transmission characteristic of the propagating SAW. In this paper, a novel SAW-based impedance sensor type is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Finally, the ATs platform can be made of a single, integrated micro-device, avoiding any moving parts and/or complicated setup procedures, which make the system very easy to use ( Guo et al, 2016 ). In this regard, the implementation of surface acoustic wave (SAW) transducers ( Ahmed et al, 2016 ) for on-chip manipulation of cells has been reported ( Voiculescu and Nordin, 2012 ; Ding et al, 2014 ; Nguyen et al, 2017 ).…”
Section: Tweezing Methodsmentioning
confidence: 99%
“…Finally, the ATs platform can be made of a single, integrated micro-device, avoiding any moving parts and/or complicated setup procedures, which make the system very easy to use ( Guo et al, 2016 ). In this regard, the implementation of surface acoustic wave (SAW) transducers ( Ahmed et al, 2016 ) for on-chip manipulation of cells has been reported ( Voiculescu and Nordin, 2012 ; Ding et al, 2014 ; Nguyen et al, 2017 ).…”
Section: Tweezing Methodsmentioning
confidence: 99%
“…, k n are regression coefficients, and e is error. Based on the simulation output data, the regression coefficients in equation (10) are solved by the least square method.…”
Section: Effect Of Idt Position Parameters On Sensor Sensitivitymentioning
confidence: 99%
“…[1][2][3][4] Because SAW sensors are particularly sensitive to the environmental changes on the substrate surface, they are widely used in the detection of physical, 5 chemical, 6 and biological 7 data. With the continuous increase in SAW sensor applications, the study of the aspects of theoretical enrichment, 8,9 working mechanism innovation, 10 simulation model improvement, 11 and working performance development 12 for SAW sensors has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%
“…To form SAM using the aliphatic thiols to modify the gold electrode surface in the biosensor design are often observed in the literature [19][20][21][22][23]. Whereas, it is seen that the use of aromatic thiols is much less in biosensor studies [24][25][26].…”
Section: Introductionmentioning
confidence: 99%